A potential role for Eph receptor signalling during migration of corneal endothelial cells. (May 2018) - Walshe, Jennifer; Richardson, Neil A.; Al Abdulsalam, Najla Khaled; Stephenson, Sally-Anne; Harkin, Damien G.
Abstract: The corneal endothelium is a monolayer of epithelial cells that lines the posterior surface of the cornea and is essential for maintenance of corneal transparency. Wound healing within the corneal endothelium typically occurs through cell spreading and migration rather than through proliferation. The mechanisms that control corneal endothelial cell migration are unclear. In this study we demonstrate that cultures of corneal endothelial cells display reduced migration in scratch wound assays, and reduced levels of E-cadherin mRNA, following suppression of ligand-activated Eph receptor signalling by treatment with lithocholic acid. Two Eph receptors, EphA1 and EphA2, were subsequently detected in corneal endothelial cells, and their potential involvement during migration was explored through gene silencing using siRNAs. EphA2 siRNA reduced levels of mRNA for both EphA2 and N-cadherin, but increased levels of mRNA for both EphA1 and E-cadherin. No effect, however, was observed for EphA2 siRNA on migration. Our results indicate a potential role for Eph receptor signalling during corneal endothelial cell migration via changes in cadherin expression. Nevertheless, defining a precise role for select Eph receptors is likely to be complicated by crosstalk between Eph-mediated signalling pathways. Highlights: The Eph inhibitor lithocholic acid suppresses corneal endothelial cell migration. Cadherin levels are regulated by Ephs in corneal endothelial cells. Reduced E-cadherin is associated with reduced corneal endothelial cell migration.